Dark fermentative hydrogen production from hydrolyzed sugar beet pulp improved by nitrogen and phosphorus supplementation. (November 2021) - Cieciura-Włoch, Weronika; Borowski, Sebastian; Domański, Jarosław
Highlights: Effect of nitrogen and phosphorus addition on hydrogen production was studied. Three salts were applied for supplementation of hydrolyzed sugar beet pulp. K3 PO4 increased hydrogen yield to 36 dm 3 /kgVS in semi-continuous experiments. Noticeable methane production was due to the activity of Methanosphaera sp. Abstract: The effect of nitrogen and phosphorous addition on hydrogen production from hydrolyzed Sugar beet pulp (SBP) was investigated using (NH4 )3 PO4, NH4 Cl and K3 PO4 as the supplements. In batch tests, the maximal hydrogen production of 279 dm 3 /kgVS was observed for K3 PO4, which was added to SBP in a dose of 1 g/dm 3 . In semi-continuous experiments, the greatest hydrogen production of 36 dm 3 /kgVS was reported for the same supplement, and this value was twice higher than that of the control run. The analysis of microbiota revealed that the majority of bacteria was affiliated to the orders Clostridiales, Lactobacillales and Coriobacteriales . Moreover, a noticeable methane production was associated with the activity of Methanosphaera sp., which could grow in a low pH environment of dark fermentation.